2019
DOI: 10.3389/fvets.2019.00308
|View full text |Cite
|
Sign up to set email alerts
|

A Pine Enhanced Biochar Does Not Decrease Enteric CH4 Emissions, but Alters the Rumen Microbiota

Abstract: The objective of this study was to examine the effect of a pine enhanced biochar (EB) on rumen fermentation, apparent total tract digestibility, methane (CH4) emissions, and the rumen and fecal microbiome of Angus × Hereford heifers fed a barley silage-based diet. The experiment was a replicated 4 × 4 Latin square using 8 ruminally cannulated heifers (565 ± 35 kg initial BW). The basal diet contained 60% barley silage, 35% barley grain and 5% mineral supplement with EB added at 0% (control), 0.5, 1.0, or 2.0% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 48 publications
1
19
0
Order By: Relevance
“…Biochar supplemented at 8 g/kg DM reduced CH 4 production by 9.5% in growing steers and 18.4% in finishing steers (Winders et al 2019). Contrary to these findings, inclusion levels of 'pine-enhanced biochar' at 5, 10 and 20 g/kg DM in the diets of Angus • Hereford heifers did not reduce CH 4 emissions (Terry et al 2019). However, it altered the microbiota, notably selecting against Fibrobacter species, which is one of the dominating phyla of the rumen responsible for cellulose degradation (Béra-Maillet et al 2004).…”
Section: Biocharmentioning
confidence: 80%
See 1 more Smart Citation
“…Biochar supplemented at 8 g/kg DM reduced CH 4 production by 9.5% in growing steers and 18.4% in finishing steers (Winders et al 2019). Contrary to these findings, inclusion levels of 'pine-enhanced biochar' at 5, 10 and 20 g/kg DM in the diets of Angus • Hereford heifers did not reduce CH 4 emissions (Terry et al 2019). However, it altered the microbiota, notably selecting against Fibrobacter species, which is one of the dominating phyla of the rumen responsible for cellulose degradation (Béra-Maillet et al 2004).…”
Section: Biocharmentioning
confidence: 80%
“…Possible mechanisms have been elucidated through a study that observed that application of biochar to paddy soils stimulated methanotrophic proteobacteria and reduced CH 4 , despite methanogens also being stimulated (Feng et al 2012). Additionally, biochar may provide a habitat for methanogens or possibly absorb gases when consumed due to its porous nature, but the mechanisms of action for CH 4 mitigation in cattle are not well understood (Terry et al 2019;Man et al 2020).…”
Section: Biocharmentioning
confidence: 99%
“…Yet, consistency seems an obvious barrier to definitive confirmation. Two recent papers ( Teoh et al, 2019 ; Terry et al, 2019 ) both used biochars with a pH similar to that applied in the current study (8.2, 7–8, and 8.4, respectively). All investigations reported no effect of the biochar on methane production.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the positive indications from in vitro experiments and theory, recent experiments with cattle fed from 0.5% to 3% of the diet as biochar made from pinewood [ 114 ] or whole pine trees [ 115 ] have failed to show significant declines in methane emissions. These latter results suggest that biochar is unlikely to have a significant impact on methane mitigation from ruminants.…”
Section: Methane Mitigation Strategiesmentioning
confidence: 99%